Impact of Influencer Endorsement on Purchase Decision: Mediating Role of Brand Image and Moderating Effect of Customer Trust - Siahaan, Febri Sari; Beryansyah, Beryansyah; Purnawan, Lesna; Hasan, Raden; Priscillia, Amanda Sona (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study examines the influence of influencer endorsement on purchase decisions for Sugarlab Face Mist products, with brand image as a mediator and customer trust as a moderator. Data were collected from 300 respondents in Jakarta and its surrounding areas, consisting of active social media users aged 18–40 years who have purchased products promoted by influencers. A purposive sampling technique was applied, and the analysis was conducted using a quantitative approach with Structural Equation Modeling based on Partial Least Squares (SEM-PLS) through Smart PLS 4.0 software. The results show that influencer endorsement significantly affects purchase decisions, both directly and through the mediation of brand image. A positive brand image strengthens consumers' purchase intentions and mediates the relationship between influencer endorsement and purchase decisions. Customer trust serves as a moderator that enhances the relationships between influencer endorsement, brand image, and purchase decisions. This study highlights the importance of influencer endorsement strategies in improving brand image and consumer purchase decisions.